Public Health Strategies for Managing Pandemics: Lessons Learned from Systematic Reviews of Recent Global Crises - AATI, MOHAMMED HAMAD AHMED; WARQASH, ABDULMOHSEN MASOUD ALI AL; ZELAEI, NAWAF ABDULRAHMAN; JAHSHAR, ABDULRAHMAN YAHA ABDULLAH; ALGHAMDI, EBTESAM IMBARAK SAFAR; MUSHAHHIM, MOHAMMED ALI ALI; ALGHAMDI, ABDULRAHMAN FAISAL MOHAMMED; ALTHOBAITI, AHMED GHAZI SAHAL; ALWADIE, ABDULLAH HASSAN HUSSEIN; ALSAGOOR, ALI SALEH (Journal of Ecohumanism, 2024)
Crisis control is daunting for any public health system worldwide, particularly in pandemics. As new acute infections continue to be identified, practicable, effective measures are important to reduce damage and facilitate healing. Against this background, this paper explores systematic reviews of pandemic responses, predominantly the COVID-19 outbreak, the Ebola outbreak, and the H1N1 influenza pandemic intervention. When combined, the result of the reviews used in this paper is the recognition of effective interventions, including early warning systems, isolation, vaccination, and healthcare infrastructure improvement. It also looks at working conditions during such crises, such as scarcity of commodities, rumors, and disparity in receiving healthcare in LMICs. Perhaps most importantly, these pandemics have provided insights into the course that future pandemics should/should not take by pointing to the importance of preparedness, cooperation, and communication. Finally and principally, this review is intended to guide public health interventions and improve control of subsequent pandemics by boosting health systems and organizational collaboration and promoting universal health access. This paper argues that there should be readiness and enhanced international collaboration if sentimental-related diseases are to be prevented.